2016
DOI: 10.12659/msm.899977
|View full text |Cite
|
Sign up to set email alerts
|

The Syndrome of Inappropriate Secretion of Anti-Diuretic Hormone (SIADH) and Brucellosis

Abstract: BackgroundOur study aimed to demonstrate the frequency of the syndrome of inappropriate ADH secretion (SIADH) and associated factors during the course of brucellosis in children and adolescents.Material/MethodsThe study included children and adolescents aged 0–18 years old diagnosed with brucellosis between 2012 and 2014. The data were collected from patient charts. The diagnosis of brucellosis was made based on titrations >1:160 in standard Wright tube agglutination tests and/or positive culture tests. SIADH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In this study, some patients (12.90%) developed hyponatremia. In addition, Bala et al [20]. proposed that hyponatremia may be caused by inappropriate secretion of the antidiuretic hormone due to infection with Brucella.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some patients (12.90%) developed hyponatremia. In addition, Bala et al [20]. proposed that hyponatremia may be caused by inappropriate secretion of the antidiuretic hormone due to infection with Brucella.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of SIADH in the setting of brucellosis was reported to be as high a 54 % [ 5 ]. A study done on pediatric patients with brucellosis revealed that brucellosis patients with SIADH have significantly higher levels of glucose, inflammatory markers, and liver enzymes [ 6 ]. Generally, fluid restriction and treating brucellosis are enough to manage brucellosis-related SIADH.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fluid restriction and treating brucellosis are enough to manage brucellosis-related SIADH. In contrast, acute symptomatic hyponatremia warrants prompt diagnosis and treatment to avoid neurological complication [ 7 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Syndrome of inappropriate secretion of ADH (SIADH), which presented with hyponatremia in a euvolemic patient without other electrolyte abnormality has been reported in patients with brucellosis. Bala et al [14] in a study of 160 children and adolescent with SIADH reported 21.9% prevalence of SIADH. Urinary sodium (>25 mmol/L) with normal dietary salt intake, low uric acid (<2 mg/dL), the absence of kidney, thyroid or adrenal disease, and history of diuretic use were the criteria for diagnosis.…”
Section: Electrolyte Abnormality In Brucella Infectionmentioning
confidence: 96%